Impact and challenges of enactment for advanced regenerative medicine in South Korea - Kim, Dong-Sook; Bae, SeungJin (Frontiers in Bioengineering and Biotechnology, 2022)
The Korean government has enacted the Act on Advanced Regenerative Medicine and Advanced Biological products (ARMAB) in August 2019, and it has been implemented in 2020. We reviewed the changes made by ARMAB compared to the existing Pharmaceutical Affairs Act and discussed future challenges to accelerate regenerative medicine while ensuring safety and efficacy. This act and regulations focused on the key elements of act as follows: the definition of advanced regenerative medicine (RM), the licensing of related facilities, safety management such as long-term follow-up, clinical research review committee, and establishment of a roadmap. Our study shows that Korea has achieved the second highest number of first approvals for regenerative medicine indications worldwide through expedited approvals encouraging innovation, while maintaining patient safety by mandating long-term follow-up. Additionally, the establishment of an interactive system for retrieval of patients' data and reporting of safety information by manufacturers electronically demonstrates Korea’s commitment to innovation for Advanced RM and patient safety.